The Implementation of Think Pair Share in Improving Students’ Speaking Ability in Giving Opinions Toward Videos or Podcasts Characters - Rasmita Rasmita; Rosi Kumala Sari (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This research aims to describe the implementation of the Think Pair Share (TPS) learning model in improving students’ speaking skills, particularly in expressing opinions about English videos or podcasts that the students have watched or listened in learning process. This research method was a descriptive qualitative with participants consisting of 42 students from first-semester students of the English management Study Program at Putra Indonesia University in Padang. Data were collected through observation, interviews, and documentation of classroom activities. The results revealed that the systematic application of the three stages of TPS—think, pair, and share—significantly improved students’ participation in giving opinion in the class. They use variation vocabulary and confidence in expressing opinions. Moreover, the model fostered a collaborative and communicative learning environment among students. Furthermore, TPS created a collaborative and communicative learning atmosphere that encouraged students to support each other and reduce anxiety in speaking English. The integration of digital media, such as videos and podcasts, also increased students’ interest and motivation in learning. Thus, implementing Think Pair Share (TPS)in speaking class proved that it is an effective and relevant strategy to enhance students’ speaking ability.